Factors Related to Sexual Intercourse Among Korean Middle and High School Students - Shim, Joohee; Baek, Jihyun; Han, Seungwoo (Frontiers in Public Health, 2022)
Background Social interest in sexual intercourse among teenagers is increasing in Korea. This study aimed to identify factors related to sexual intercourse among adolescents. Methods This is a secondary analysis study using data from the 2020 Korea Youth Risk Behavior Survey, with information regarding 54,948 middle school and high school students in Korea having been analyzed. Demographics, health behavior, and mental health characteristics were included. Data evaluation involved chi-square test and binary multivariable logistic regression analysis. Results For middle school students, sexual intercourse was related to their housing type [Odds Ratio (OR) = 10.698], smoking (OR = 5.165) and drinking (OR = 2.229) experience, suicide attempt (OR = 1.920), gender (OR = 1.632), loneliness (OR = 1.501), sadness and despair (OR = 1.493), year level (OR = 1.457), happiness (OR = 0.772), sleep status (OR = 0.716), economic status (OR = 0.705). For high school students, sexual intercourse was related to their smoking experience (OR = 4.746), housing type (OR = 3.661), drinking experience (OR = 2.840), drug use (OR = 2.511), suicide attempt (OR = 2.071), year level (OR = 1.989), sadness and despair (OR = 1.506), gender (OR = 1.429), suicide plan (OR = 1.402), loneliness (OR = 1.270), academic performance (OR = 1.165), happiness (OR = 0.865), subjective health status (OR = 0.814), and economic status (OR = 0.727). However, sleep status was statistically significant for middle school students, but not for high school students. Academic performance, drug use, suicide plan, and subjective health status were statistically significant in high school students, but not in middle school students. Conclusion A program that can directly mediate these factors must be prepared. When conducting sex education for adolescents, mental health-related factors must also be considered.